Lipid polymer hybrid nanocarriers: Insights into synthesis aspects, characterization, release mechanisms, surface functionalization and potential implications - Shah, Saurabh; Famta, Paras; Raghuvanshi, Rajeev Singh; Singh, Shashi Bala; Srivastava, Saurabh (Colloid and interface science communications, 2022)
Lipid polymer hybrid nanoparticles (LPHN) are novel systems which are potentially emerging in the era of nano-medicine. They are core-shell nanostructures which comprise of polymer and phospholipids used in the preparation of polymeric nanoparticles and liposomes respectively. This combinatorial venture bequeaths combined attributes of nanoparticles and liposomes with respect to enhanced stability, biocompatibility and cellular uptake. Current review encompasses deeper insights into the types of LPHN, synthesis aspects and their characterization, release mechanisms and surface functionalization. The article potentiates the noteworthy applications of LPHN in the field of drug delivery and targeting along with the hurdles hindering their transition from bench to bedside. The scope of LPHN in various fields and their tunability towards various applications have been depicted. [Display omitted] •LPHN are new age carrier systems which overcome the drawbacks of liposomes and nanoparticles.•Different types and preparation techniques of LPHN were discussed.•Characterization techniques and different release mechanisms were deliberated.•Importance of surface functionalization and circumvention of clinical translation barriers has been conveyed.